`SERIKANDI TERAKHIR' 3D GAME FOR GIRLS - Vidaranieta, Apin (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Nowadays. computer games not only act as an entertainment tools, it is also act as a medium that could attract an individual to involved in computing career seriously. There are many computer games that commercialized in global industry and brought huge profit to the developer. The situation here is most of the gamers are boys and this lead to one question, it is true girls not interested in game play? " by previous research, it was found that most of girls did not attract to computer games because most of it seems boys-oriented; war, blood-scene, destruction and time defeat games' type. This project comes out to get ideas or formula for designing game for girls. By gain information from many resources, proposed solution due to this problem will be listed. A simple 3D game also created for applying the proposed solution